The Central Nervous System of Vertebrates 1998
DOI: 10.1007/978-3-642-18262-4_22
|View full text |Cite
|
Sign up to set email alerts
|

Mammals

Abstract: Introduction (Voogd) 0 o 0 o o o o 0 Gross Morphology of the Mammalian Brain 0 0 0 o 0 o o o o 0 Frame 1 Lateral Views of the Brains of Selected Mammals Spinal Cord (Voogd) 0 o o o o o o o o Gross Anatomy, Ascensus Medullae Grey matter 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 Primary Afferent Fibres and the Dorsal Funiculus

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
107
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(109 citation statements)
references
References 2,068 publications
(1,684 reference statements)
2
107
0
Order By: Relevance
“…Projecting laterally from each hemisphere is a paraflocculus with dorsal and ventral limbs (Larsell, 1970). In canids, glires, and marsupials, part or all of the ventral paraflocculus, known as the petrosal lobule, is situated in a bony concavity, called the subarcuate fossa, on the endocranial surface of the petrosal (Larsell, 1970;Evans and Christensen, 1979;Voogd et al, 1998). Both the subarcuate fossa and the paraflocculus vary in size.…”
Section: Review Of Soft Tissues Associated With the Petrosalmentioning
confidence: 99%
See 1 more Smart Citation
“…Projecting laterally from each hemisphere is a paraflocculus with dorsal and ventral limbs (Larsell, 1970). In canids, glires, and marsupials, part or all of the ventral paraflocculus, known as the petrosal lobule, is situated in a bony concavity, called the subarcuate fossa, on the endocranial surface of the petrosal (Larsell, 1970;Evans and Christensen, 1979;Voogd et al, 1998). Both the subarcuate fossa and the paraflocculus vary in size.…”
Section: Review Of Soft Tissues Associated With the Petrosalmentioning
confidence: 99%
“…Both the subarcuate fossa and the paraflocculus vary in size. Cetaceans have relatively large paraflocculi (Voogd et al, 1998) but lack a subarcuate fossa.…”
Section: Review Of Soft Tissues Associated With the Petrosalmentioning
confidence: 99%
“…6E). It has been shown that jaw-closing and jaw-opening motoneurons are distributed in the dorsolateral and ventromedial divisions, respectively, of the MoV in mammals (Mizuno et al 1975;Voogd et al 1998). In rats, the dorsolateral division exists at the whole rostrocaudal level of the MoV, whereas the ventromedial division is found only at the caudal half of the MoV (Jacquin et al 1983;Sasamoto 1979;Uemura et al 2007).…”
Section: Properties Of Supv Neurons Projecting To the Movmentioning
confidence: 99%
“…The lateral component of the somatic motor system consists of descending systems that control the motoneurons innervating distal body muscles, i.e., arm, hand, leg, feet, but also orofacial muscles. Examples of descending systems belonging to the lateral component of the somatic motor system are the rubrospinal tract, albeit that this pathway is of minor importance in humans (Voogd et al, 1998), and the corticobulbospinal tracts originating in the motor and premotor cortex (for reviews, see Kuypers 1981;Holstege, 1991).…”
mentioning
confidence: 99%